HUBUNGAN ANTARA PENGETAHUAN IBU TENTANG IMUNISASI LANJUTAN DENGAN STATUS IMUNISASI PADA ANAK USIA 25-30 BULAN - Suartini, Ni Wayan; Erawati, Ni Luh Putu Sri; Budiani, Ni Nyoman (Journal of Innovation Research and Knowledge, 2025)
Abstract: Immunization is an effort to increase the body's immunity to disease. In Puskesmas Selat in 2023, measles booster immunization coverage reached 91.27% and DPT booster 92.46% for children aged 25-30 months. This study aims to determine the relationship between the level of maternal knowledge about follow-up immunization and the immunization status of children aged 25-30 months at Puskesmas Selat. The study used a cross-sectional method with a sample of mothers who had children aged 25-30 months. Data was collected in September-November 2024 through questionnaires and MCH book, using random sampling technique. A total of 65.9% of respondents had good knowledge, while 34.1% were less good. Complete immunization status was found in 78% of respondents, while 22% were incomplete. Chi-square analysis showed a significant relationship between maternal knowledge and immunization status (p<0.001). In conclusion, there is a relationship between maternal knowledge about follow-up immunization and immunization status of children aged 25-30 months. It is hoped that further education can improve maternal knowledge and encourage complete immunization.